Advances in food rheology and its applications - Ahmed, Jasim, 1966-; Ptaszek, Pawel; Basu, Santanu (Woodhead Publishing in food science, technology and nutrition, 2017)
"This book presents in-depth and state-of-the-art coverage of the measurement and application of food rheology as a critical tool for food companies when characterizing ingredients and final products and predicting their performance and consumer acceptance"--Resumé vydavatele